DUOX2 and DUOXA2 Variants Confer Susceptibility to Thyroid Dysgenesis and Gland-in-situ With Congenital Hypothyroidism - Wang, Fengqi; Zang, Yucui; Li, Miaomiao; Liu, Wenmiao; Wang, Yangang; Yu, Xiaolong; Li, Hua; Wang, Fang; Liu, Shiguo (Frontiers in Endocrinology, 2020)
Background: Thyroid dysgenesis (TD), which is caused by gland developmental abnormalities, is the most common cause of congenital hypothyroidism (CH). In addition, advances in diagnostic techniques have facilitated the identification of mild CH patients with a gland-in-situ (GIS) with normal thyroid morphology. Therefore, TD and GIS account for the vast majority of CH cases. Methods: Sixteen known genes to be related to CH were sequenced and screened for variations by next-generation sequencing (NGS) in a cohort of 377 CH cases, including 288 TD cases and 89 GIS cases. Results: In our CH cohort, we found that DUOX2 (21.22%) was the most commonly mutated pathogenic gene, while DUOXA2 was prominent in TD (18.75%) and DUOX2 was prominent in GIS (34.83%). Both biallelic and triple mutations of DUOX2 were found to be most common in children with TD and children with GIS. The most frequent combination was DUOX2 with DUOXA1 among the 61 patients who carried digenic mutations. We also found for the first time that biallelic TG, DUOXA2 and DUOXA1 mutations participate in the pathogenesis of TD. In addition, the variant p.Y246X in DUOXA2 was the most common mutational hotspot, with 58 novel mutations identified in our study. Conclusion: We meticulously described the types and characteristics of mutations from sixteen known gene in children with TD and GIS in the Chinese population, suggesting that DUOXA2 and DUOX2 mutations confer susceptibility to TD and GIS via polygenic inheritance and multiple factors, which further expands the genotype-phenotype spectrum of CH in China.